Visitor’s Perception About Orangutan Conservation In Indonesian Zoos - Nurzaidah Putri Dalimunthe; Hady Sukadi Alikodra; Entang Iskandar; Sri Suci Utami Atmoko; Rahmad Lingga (International Journal of Science, Technology & Management, 2021)
Zoos have four main roles namely conservation, research, education and recreation. Whether the existence of the zoo has succeeded in increasing or at least influencing people's perceptions of animal conservation should be investigated further. The research aimed to assess the image of the zoos and perception of the visitors about orangutan conservation. This study applied the questionnaire and methods to Indonesia zoo's, and examines the effect of the zoo at changing visitor's conservation awareness. The result showed that there were no significant difference acros the sites and between arrival dan departures. This could be caused by many reasons, for example the short visit time, minimal information obtained during the visit or the background of the visitors themselves.